The Methodology and Style of Imām Qudūrī in Kitāb al Tajrīd: A Research Study in the Light of ’Ilm al Khilaf - Sani, Hafiz; Shaid, Bakht (Journal of Islamic and Religious Studies, 2016)
Since the creation of this world, there have been disagreements in different matters among mankind. Technically, difference in opinion is of two kinds .One is Invalid or unpleasant disagreement; which has no valid reasoning and it bases on other evil objectives. While the other one is valid or pleasant disagreement; which bases on valid reasoning. The second one is also known as healthy disagreement. The disagreements among Islamic Scholars, ‘Ulamā and fuqahā relates to the second kind; valid disagreements, because they are established on valid reasons and evidences. They are also considered as a blessing for mankind. That is why these scholarly and fiqhī disagreements are always deeply admired. An important book scholarly written on the subject matter is ‘Kitāb al Tajrīd’ by Imām Qudūrī. This article is an introduction to his book ‘Kitāb al Tajrīd’ and its style. It is a distinct and excellent book of its kind. The features of the book motivate to discuss about it.